Exploratory Study on Personal Finance in the Context of COVID-19 - Deyanira Bernal-Domínguez; José G. Vargas-Hernández (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The world is currently experiencing a dramatic crisis that has not yet reached bottom. Only in Mexico in the second quarter of 2020 there was a drop in the Gross Domestic Product of -18.9% compared to the same quarter of 2019. Derived from the economic effects of the pandemic Covid19 among other factors. In this context, the objective is to identify types of personal expenses in households located in Culiacán, Sinaloa, Mexico as of July 15, 2020, for which an exploratory study was carried out; 488 surveys with 48 items were applied electronically. The main results were that most of the respondents’ budget, spend according to their income, have had no problem paying their bank loans on time, would consider a fund for future contingencies, have not purchased health insurance, have not bought a computer or cell phone among other issues analyzed. The limitations were that the surveys were applied to the social network contacts of the person in charge of this study. The main findings are oriented to the fact that the studied population has not acquired additional medical insurance despite the pandemic. It is also concluded that the population under study has become aware of having savings for contingency funds and that digital life still shows resistance in making personal financial decisions.